Understanding psychrometrics - Gatley, D. P. (ASHRAE, 2013)
"Updates the second edition to provide readers a reference that agrees with the latest international standards. The third edition also includes a revised equation for the adiabatic saturation process, an summary of the 2009 RP-1485 ASHRAE research, as well as minor edits to the text"